Arthroscopic Reconstruction of the Anterior Cruciate Ligament: Comparison between One Day Surgery Care with Remnant Preserving Technique and Conventional Care with Standard Technique - Thitirungruang, MD, Kantanop (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To compare the outcomes of different methods after arthroscopic ACL reconstruction. The two methods used are: one-day surgery care method, using remnant preserving ACL reconstruction technique, and the conventional care method, using standard ACL reconstruction technique. Patients and Methods: The sample groups include: patients admitted into the orthopedics department at Chonburi Hospital from September 1st, 2017 to June 30th, 2018. The sample groups were divided into experimental (one day surgery care and remnant preserving ACL reconstruction) group of 30 patients and control (conventional care and standard ACL reconstruction) group with 32 patients. The comparison was made on the basis of: scoring of pain after surgery, costs of hospital care, amount of bleeding in the first 24 hours, surgical operation time, postoperative wound infections, and days admitted in the hospital. Results: There were significant difference between postoperative pain (p=0.025), costs of hospital care (p=0.00), amount of bleeding in 24 hours (p=0.00), and amount of days admitted in the hospital (p=0.00). However, the operation time and postoperative wound infections, showed no significant differences. Conclusion: The one-day surgery care, using remnant preserving ACL reconstruction technique, has a better outcome than the conventional care method, using standard ACL reconstruction technique. Furthermore, the one-day surgery care method can be improved and further developed for outpatient care as well.